2010
DOI: 10.1103/physrevb.82.214403
|View full text |Cite
|
Sign up to set email alerts
|

Detection and quantification of inverse spin Hall effect from spin pumping in permalloy/normal metal bilayers

Abstract: Spin pumping is a mechanism that generates spin currents from ferromagnetic resonance over macroscopic interfacial areas, thereby enabling sensitive detection of the inverse spin Hall effect that transforms spin into charge currents in nonmagnetic conductors. Here we study the spin-pumping-induced voltages due to the inverse spin Hall effect in permalloy/normal metal bilayers integrated into coplanar waveguides for different normal metals and as a function of angle of the applied magnetic field direction, as w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
477
5
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 509 publications
(527 citation statements)
references
References 45 publications
41
477
5
4
Order By: Relevance
“…In addition, it has relatively poor spin scattering efficiency due to relatively long spin diffusion length of 10 nm [31] as compared to Pt (3.5 to 10 nm) [19,20]. This is corroborated by the increase in the value of the inhomogeneous broadening H 0 .…”
Section: …(4)supporting
confidence: 55%
See 1 more Smart Citation
“…In addition, it has relatively poor spin scattering efficiency due to relatively long spin diffusion length of 10 nm [31] as compared to Pt (3.5 to 10 nm) [19,20]. This is corroborated by the increase in the value of the inhomogeneous broadening H 0 .…”
Section: …(4)supporting
confidence: 55%
“…In addition, it affects the damping properties critically by various seed and capping layers. Recently, research has been focussed to understand the effect of heavy metal as seed and capping layers [17][18][19][20][21][22]. In a recent report Tokac et al [21] have shown that the effective spin conductance mixing strongly depends on the interfaces of seed (Ta/Cu) and capping (Cu or Ir) layers.…”
Section: Introductionmentioning
confidence: 99%
“…SHE depends on the SOC and θ SH is a measure of the strength of SOC. Because of the generally accepted Z 4 dependence of SOC, measurement of θ SH has been focused on heavy elements by SHE [8] or inverse spin Hall effect (ISHE) [9][10][11][12][13][14][15], while 3d metals have rarely been studied [16,17].…”
mentioning
confidence: 99%
“…Ferromagnetic resonance (FMR) spin pumping of pure spin currents from a ferromagnet (FM) into a nonmagnetic (NM) material provides a powerful technique for measurement of θ SH in a broad range of materials [7,9]. We report a systematic study of the ISHE in a series of 3d transition metals using FMR spin pumping from Y 3 Fe 5 O 12 (YIG) epitaxial films into Ti, V, Cr, Mn, Fe 50 Mn 50 (FeMn), Fe 20 Ni 80 (Py), Ni, and Cu.…”
mentioning
confidence: 99%
See 1 more Smart Citation